Evaluation of changes in forest cover in the Huacamayo - Montenegro Pisfil, Jaime Federico (2022)
The objective of this research work was to evaluate the transformation of the forest area in the Huacamayo River Micro-basin. 6 Landsat satellite photographs from the years 1999, 2010, 2014, 2016, 2018, 2020 were used. During 1999-2010 a loss of 13.5 km2 of forest cover was observed, the periods 2014, 2018, 2020, showed progressive retreat of the forest tropical humid, 4.4 km2, 3.1 km2 and 7.5 km2, respectively. In the 21 years, 28.5 km2 of forest in the Micro-basin have been lost, reporting a percentage of deforestation -1.2% per year; Between 1999-2010, the highest deforestation rate was observed, -1.7%. For the year 2031, the model for the tropical forest in the Microbasin estimated a resulting area of 39 km2, demonstrating its progressive decrease. This study will guide the conservation and management of the forest area of the Microbasin.